2014
DOI: 10.1158/1535-7163.mct-13-0558
|View full text |Cite
|
Sign up to set email alerts
|

Superior Antitumor Activity of a Novel Bispecific Antibody Cotargeting Human Epidermal Growth Factor Receptor 2 and Type I Insulin-like Growth Factor Receptor

Abstract: The humanized anti-HER2 monoclonal antibody (mAb) trastuzumab (Herceptin; Genentech) effectively inhibits human epidermal growth factor receptor 2 (HER2)-positive breast tumors. However, many patients responding to treatment often develop resistance. Cross-talk between type I insulin-like growth factor receptor (IGF-IR) and HER2 and elevated IGF-IR signaling have been implicated in tumor cell resistance to trastuzumab therapy. Previously, we reported that the anti-IGF-IR mAb m590 inhibits proliferation and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…In trastuzumab-resistant cells, IGF1R-promoted ERBB2 phosphorylation and IGF1R-induced invasion are mediated by Src and FoxM1 ( 98 ). Co-targeting ERBB2 and IGF1R reduces Erk/AKT activation, cell proliferation, in vitro invasion, and xenograft tumor growth to a greater extent than targeting either receptor individually ( 98 , 99 ). Interestingly, treating trastuzumab-resistant cells with metformin re-sensitizes cells by disrupting the ERBB/IGF1R complexes ( 97 ), again strongly suggesting that a combined therapy would hold promise for patients with ERBB2 + breast tumors.…”
Section: Igf1r Across Breast Cancer Subtypesmentioning
confidence: 99%
“…In trastuzumab-resistant cells, IGF1R-promoted ERBB2 phosphorylation and IGF1R-induced invasion are mediated by Src and FoxM1 ( 98 ). Co-targeting ERBB2 and IGF1R reduces Erk/AKT activation, cell proliferation, in vitro invasion, and xenograft tumor growth to a greater extent than targeting either receptor individually ( 98 , 99 ). Interestingly, treating trastuzumab-resistant cells with metformin re-sensitizes cells by disrupting the ERBB/IGF1R complexes ( 97 ), again strongly suggesting that a combined therapy would hold promise for patients with ERBB2 + breast tumors.…”
Section: Igf1r Across Breast Cancer Subtypesmentioning
confidence: 99%
“…50 Co-targeting HER-2 and IGF-1R with trastuzumab and heat-induced expression of dominant-negative IGF-1 receptor (486/STOP) has been shown to synergistically inhibited human breast cancer cells. 16 Further, synergistic antitumor effects were reported with the combination of trastuzumab and the IGF-1R kinase inhibitor NVP-AEW541 preferentially in human breast cancer cells that are HER-2-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a preclinical study indicated that combined treatment with IGF-1R-and HER-2-targeted therapies resulted in synergistic growth inhibition 22 of breast cancers, findings that have encouraged the development of a novel HER-2:IGF-1R bispecific antibody. 23 Further, we previously showed that IGF-1R-targeting improves trastuzumab sensitivity in cells that have acquired trastuzumab resistance. 17 Thus, targeting the IGF-1R signaling axis is a promising strategy, partly because it has the potential to bypass multiple mechanisms that promote resistance to currently employed targeted therapies against breast cancer.…”
Section: Introductionmentioning
confidence: 98%
“…Chen et al developed an antibody bispecific for HER2 and IGF-1R[63]. They demonstrated that this construct inhibits tumor growth in mouse models.…”
Section: Signaling Disruptionmentioning
confidence: 99%